Kenntnisstand der Bevölkerung über Leitsymptome kardiovaskulärer Notfälle und Zuständigkeit und Erreichbarkeit von Notrufeinrichtungen: Ergebnisse der KZEN-Studie in der Westpfalz = Knowledge of the population about leading symptoms of cardiovascular emergencies and the responsibility and accessibility of medical facilities in emergencies : results of the KZEN study in Western Palatinate - Luiz, Thomas; Madler, Christian (Der Anaesthesist, 2017)
BackgroundThe Westpfalz is a mainly rural region in the southwestern part of the German state of Rhineland-Palatinate with 527,000 inhabitants and demonstrates a higher than average cardiovascular mortality compared to the rest of Germany. The reasons are not known. Our study attempted to investigate whether significant deficits in knowledge of the population on cardiovascular emergencies, the accessibility of emergency medical services (EMS) or the different responsibilities and abilities of the medical facilities could be held responsible for this. These factors are of the utmost importance for the timely initiation and administration of curative therapeutic strategies.MethodsWe conducted standardized telephone interviews with 1126 inhabitants of Westpfalz as a representative sample of the population in the study area. The interviewees were asked about demographic data, participation in first aid courses, knowledge of emergency telephone numbers and the different responsibilities of preclinical emergency physicians which are a part of the EMS and the doctor-on-call system for non-life-threatening conditions (ÄBD). Moreover, we asked about the leading symptoms of myocardial infarction and stroke. Finally, we enquired how the respondents would react in fictitious cardiovascular emergencies.ResultsOf the participants 651 (57.8%) were female and 475 (42.2%) male. The mean age in our study was 51 ± 18 years and 1002 of the participants (89%) had some formal first aid training. The current telephone number of the EMS system (112) was known to 29.5% of the interviewees and 15.4% could only recall the old number (19222) which is no longer in use. In the case of participants who gave the correct telephone number the first aid course took place 10 years ago (median), whereas for participants who did not know the correct number, the course dated back 15 years (median, p < 0.01). The telephone number 116117 of the ÄBD, usually a family physician, was familiar to only 23 of the people interviewed (2.0%). The basic differences in the functions and responsibilities of the ÄBD and the emergency physician within the EMS were known to only 235 participants (20.2%), 231 (20.5%) were not able to name a single leading symptom of a myocardial infarction and 354 did not know a leading symptom (31.4%) of stroke. In the fictitious case report of an unconscious patient with respiratory arrest (as a sign of cardiac arrest) 96.8% of the interviewees would have correctly informed the EMS, for patients with acute coronary syndrome 81.8% and for a stroke patient 76.8% (cardiac arrest vs. acute coronary syndrome: p < 0.001, cardiac arrest vs. stroke: p < 0.001, acute coronary syndrome vs. stroke: p = 0.005).Conclusion and recommendationsA large proportion of the population were found to be ignorant about the telephone numbers for medical emergency calls and the different functions of the ÄBD and emergency physicians within the EMS. Moreover, our results indicate that a significant percentage of the population would neither be in a position to recognize a stroke or myocardial infarction in an emergency situation nor be informed enough to communicate with the correct part of the emergency system. The association of these deficits with the time elapsed since the last first aid course should be reason enough to continuously motivate the population, especially at risk patients and their relatives, to repeat such courses several times. Furthermore, digital media should be used more intensively in providing first aid instructions. In our opinion, this study clearly shows that in Germany a uniform number for medical emergency calls is mandatory.